6(10-х)(3х+4)=0 2(5х-7)(1+х)=0 (3х+18)(2-х)=0 (6-х)(5х+40)=0

6(10-х)(3х+4)=0 2(5х-7)(1+х)=0 (3х+18)(2-х)=0 (6-х)(5х+40)=0
Гость
Ответ(ы) на вопрос:
Гость
6(10-х)(3х+4)=0 10-x=0    или  3x+4=0  x=10    3x=-4               x=-4/3    2) 2(5х-7)(1+х)=0      (5x-7)=0   или (1+x)=0       5x=7                 x=-1       x=7/5      3) (3х+18)(2-х)=0   x=-6; x=2;   (6-х)(5х+40)=0 6-x=0   или   5x+40=0 x=6                  5x=-40                         x=-8          
Не нашли ответ?
Ответить на вопрос
Похожие вопросы